2020
DOI: 10.1016/j.ijnurstu.2019.103446
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nurse managers' leadership style and patients' perception of the quality of the care provided by nurses: Cross sectional survey

Abstract: The relationship between nurse managers' leadership style and patients' perception of the quality of the care provided by nurses: Cross sectional survey',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 60 publications
2
71
1
1
Order By: Relevance
“…For many health professionals, their commitment to their work and professional career is a priority that takes them away from family and social relationships and causes them to dedicate less time than they would like to family responsibilities [116]. This extreme and rigid dedication causes a high level of exhaustion and a sensation of lethargy and depersonalization [117]. The debate on the effects of this professional dedication on WLB as one's health care career advances has a long history, but the issue seems far from a closed topic [118].…”
Section: Discussionmentioning
confidence: 99%
“…For many health professionals, their commitment to their work and professional career is a priority that takes them away from family and social relationships and causes them to dedicate less time than they would like to family responsibilities [116]. This extreme and rigid dedication causes a high level of exhaustion and a sensation of lethargy and depersonalization [117]. The debate on the effects of this professional dedication on WLB as one's health care career advances has a long history, but the issue seems far from a closed topic [118].…”
Section: Discussionmentioning
confidence: 99%
“…reduction in mortality rates, decreased inpatient falls and medication errors, decreased cases of fractures and reduction in the complications regarding immobility) (Wong, Cummings, & Ducharme, 2013; Agnew & Flin, 2014; Wong & Giallonardo, 2013); and organisational outcomes (e.g. increased organisational performance and productivity) (Zaghini et al., 2020; Cumming et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by De Simone et al (2018) and Zaghini et al (2020) provides support for these ndings, i.e. both of these studies reported correlations between patient satisfaction and nurses' job satisfaction (54,55). Nurses are motivated to provide high-quality care (48); as such, it is logical that patient satisfaction with the outcomes of care will improve nurses' job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 94%